2015
DOI: 10.31631/2073-3046-2015-14-2-80-87
|View full text |Cite
|
Sign up to set email alerts
|

Measles Epidemic Process in Various Vaccinal Periods

Abstract: The considerable factual data enabled us for the first time to reveal the peculiarities of measles epidemic process manifestations in different stages of the prophylaxis. It was shown that some determinants of measles epidemic process changed during the period of high measles vaccination coverage of children and adult population: measles mortality was eliminated, the seasonal factors do not influence on the dynamics of epidemic process within a year, fluctuations of measles incidences became stochastic over ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This trend is associated with a decrease in the level of population immunity. Although it is generally accepted that the live attenuated measles vaccine is highly effective, and especially two doses of the vaccine guarantee protection against the disease in 94.1% of cases, the intensity and duration of post-vaccination immunity may be lower compared to the level of immunity acquired after an infection with a wild-type virus, since annually 15–20% of cases fall on vaccinated and revaccinated persons, and in some years their share is up to 30% ( 6 , 7 ). When examining more than 1,000 children in Canada, it was revealed that the titer of measles antibodies in them falls by an average of 5.6%, that is, the intensity of measles immunity will be almost halved over 12 years ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…This trend is associated with a decrease in the level of population immunity. Although it is generally accepted that the live attenuated measles vaccine is highly effective, and especially two doses of the vaccine guarantee protection against the disease in 94.1% of cases, the intensity and duration of post-vaccination immunity may be lower compared to the level of immunity acquired after an infection with a wild-type virus, since annually 15–20% of cases fall on vaccinated and revaccinated persons, and in some years their share is up to 30% ( 6 , 7 ). When examining more than 1,000 children in Canada, it was revealed that the titer of measles antibodies in them falls by an average of 5.6%, that is, the intensity of measles immunity will be almost halved over 12 years ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…A single measles vaccination altered some of the characteristics of the epidemic process of infection. The incidence decreased by almost 5 times in various age and social groups of the population, there was a slight increase in the inter-epidemic period and a decrease in the duration of the seasonal rise in incidence [4].…”
Section: Introductionmentioning
confidence: 89%
“…Major measles epidemics occurred every 2-3 years and resulted in more than 2.6 million deaths. The disease cyclically ranged from 50 to 1200 cases per 100,000 people per year, in one focus of the disease, on average, there were 30 cases, the proportion of foci of the disease with a prevalence of 17%, lethality involved 0.15% [2, 3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The epidemic situation with airborne infections regulated by specific preventive means remains tense. Cases of measles, rubella and mumps are discovered both among unvaccinated and vaccinated people 2 . Internal and external migration of global population, environmental disasters and globalization contribute to the rapid spread of viruses, outbreaks 3 .…”
Section: Introductionmentioning
confidence: 99%